REVISITING CONFUCIAN BUREAUCRACY: ROOTS OF THE KOREAN GOVERNMENT'S CULTURE AND COMPETITIVENESS. (18th September 2013) - Im, Tobin; Campbell, Jesse W.; Cha, Seyeong
SUMMARY: This paper looks at Korea's Chosun dynasty bureaucracy and the Neo‐Confucian principles that formed the basis of its governing philosophy. We argue that Korea's traditional bureaucracy had a number of modern characteristics, including a system of formal and informal checks on the powers of the sovereign and a decision‐making system that encouraged deliberation among highly qualified civil servants. On the basis of this exposition, we also argue that there are strong links between the traditional bureaucracy and its current, modern form. We firstly show how the institutionalization of a strong state during the period of rapid development was as much a return to traditional governing principles as it was a revolution and, secondly, how contemporary organizational culture is shaped by Korea's Confucian heritage. In the final section, we argue that the distinctive characteristics of the Korean bureaucracy have played an important role in limiting the success of a number of Western‐oriented reform efforts. Copyright © 2013 John Wiley & Sons, Ltd.